EMBOSSED NEMATODES PARASITIC IN ARTIFICIAL BIOCENOSES AND THEIR DESCRIPTION - E. Abdurakhmanova (Web of Journals Publishing, 2024)
Parasitic nematodes are one of the main pests causing damage to agricultural crops. Therefore, the study of their structure, bioecology and distribution characteristics is considered a necessary factor that helps to increase productivity and quality.
Keywords: Root knot nematodes, Meloidogyne incognita, Meloidogyne Güeldi, sexual dimorphism, stylet, bulb